AN ANALYSIS OF THE USE OF ACCURATE ACCOUNTING SOFTWARE IN IMPROVING THE EFFICIENCY AND EFFECTIVENESS OF FINANCIAL REPORTING AT PERUMDA TUNAS MALANG - Vinda Amira Ramadhani; Akie Rusaktiva Rustam (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: Digital transformation in the public sector encourages Regional Government-Owned Enterprises (BUMD) to adopt technology-based accounting information systems to enhance financial accountability and reporting quality. This study aims to analyze the use of Accurate Accounting Software in improving the efficiency and effectiveness of financial reporting at Perumda Tunas Malang, which previously experienced technical constraints with a Local Area Network (LAN)-based system. Method: The research employs a qualitative approach through in-depth interviews and field observation with five key informants, analyzed using the Miles and Huberman interactive model. The theoretical framework is grounded in the DeLone & McLean (2003) Information Systems Success Model as the primary framework, with Romney & Steinbart (2018) as a conceptual reference. Results: The system accelerates financial report preparation and strengthens real-time data-based decision-making. Challenges identified include internet connectivity dependency, limited user training, and absence of an independent backup procedure. The average user satisfaction score of 8.9 out of 10 indicates that Accurate delivers significant benefits and is worthy of further development. Novelty: Findings indicate that Accurate has been implemented through a cloud-based hybrid system with multi-account segregation of duties, capable of performing core Accounting Information System functions including data processing, standard financial statement presentation, audit trail, and internal control.